The effect of internal control weakness under section 404 of the Sarbanes-Oxley Act on audit fees - CHOI, Jong-Hag (Institutional Knowledge at Singapore Management University, 2010)
In this paper, we investigate the effect of the enactment of the SarbanesOxleyAct (SOX) in 2002 on audit pricing, using a sample of 252 firms that received an “Ineffective” audit opinion and other firms that received cleanaudit opinion on the effectiveness of the internal control over financial reportingunder Section 404 of SOX. Our analyses show the following. First,we find that auditors charge significantly higher audit fees for all firms inthe post-SOX period than in the pre-SOX period. Second, we find that auditors’opinions on the weakness in internal control (WIC) are positively associatedwith audit fees, and that the positive association between the twois pronounced primarily in the post-SOX period, but not in the pre-SOXperiod. Third, we find that clients with WIC problems that are highly leveredand/or report losses pay incrementally higher audit fees during the postSOXperiod. We also find that Big 4 audit fee premiums increase significantlyfor all clients during the post-SOX period, regardless of whether theclients have WIC or not. Overall, our results suggest that auditors, in termsof their behavior and pricing mechanism, responded to an upward shift inthe strength of the legal liability regime caused by the SOX enactment.